Human resource management - Dessler, Gary (Pearson, 2005)
This classic, readable book does the best job at covering the current issues within HRM, and provides a complete, comprehensive review of essential personnel management concepts and techniques. Considering the intensely competitive nature of business today, this book focuses on practical applications that all managers can use to deal with their HR-related responsibilities, while being able to defend their plans and contributions in measurable terms. A five-part format begins with an introduction, and then covers recruitment and placement, training and development, compensation, and labor relations and employee security. For all human resource personnel and managers.